Pengaruh Tingkat Upah, Kesejahteraan, Dan Loyalitas Terhadap Kinerja Karyawan Pada PT. POS Indonesia Kantor POS Kota Banda Aceh - Rizki , Kemal; mailisasafitri, husnaina; umar, Zulkifli (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
The purpose of this study was to determine the Effect of Wage Level, Welfare and Loyalty on Employee Performance at PT. Pos Indonesia, Banda Aceh City Post Office. The approach used in this study is quantitative. Data were collected through a questionnaire using a Likert scale as a measuring tool, the number of respondents was 70 employees, then analyzed using multiple linear regression methods, F tests and T tests to determine the effect simultaneously and partially of independent variables on dependent variables using SPSS software version 26. The results of the study based on simultaneous tests showed that the variables of wage level, welfare, and loyalty had a significant effect on employee performance at PT. Pos Indonesia, Banda Aceh Post Office. While partially the variable wage level had a significant effect on employee performance at PT Pos Indonesia, welfare had a significant effect on employee performance at PT. Pos Indonesia, Banda Aceh Post Office, and loyalty had a significant effect on employee performance at PT Pos Indonesia, Banda Aceh Post Office.